Variations in the response of different provenances of Pinus caribaea var. Hondurensis in embryo culture and callus production - Go, N. E. (Animo Repository, 1992)
The response of different provenances of Pinus caribaea var. hondurensis cultured in vitro was investigated. Emryos of slow-growing and fast-growing provenances were cultured in modified Murashige and Skoog Medium supplemented with different concentrations of BAP at different exposure periods. After the induction period, the embryos were transferred to either full- or half-strength basal medium. Results showed that the formation of adventitious buds was significantly affected by concentration of BAP in the fast-growing (Queensland and Guanja) but not in the slow-growing (Los Limones and La Mosquitia provenances. Further, adventitious bud initiation and shoot elongation were faster in the fast-growing provenances. Callus production of needles from regenerated shoots differ among the provenances tested. More rapidly growing callus lines were obtained from the slow-growing provenances, La Mosquitia, than from the fast-growing provenances, Guanaja and Queensland.